Proximal soil sensing - McBratney, Alex B.; Minasny, Budiman; Viscarra Rossel, Raphael A. (Progress in soil science, 2010)
Proximal Soil Sensing presents a comprehensive account of data acquisition using proximal soil sensors. The text discusses high resolution digital soil mapping, which uses optical, geophysical, electrochemical, mathematical and statistical methods to collect information on soil